Effects of E-Liquids and Their Aerosols on Biofilm Formation and Growth of Oral Commensal Streptococcal Communities: Effect of Cinnamon and Menthol Flavors - Nicole Christian; Daniel Burden; Alexander Emam; Alvin Brenk; Sarah Sperber; Michael Kalu; Giancarlo Cuadra; Dominic Palazzolo (MDPI AG, 2024)
(1) Background: The rise in electronic cigarette (E-cigarette) popularity, especially among adolescents, has prompted research to investigate potential effects on health. Although much research has been carried out on the effect on lung health, the first site exposed to vaping-the oral cavity-has received relatively little attention. The aims of this study were twofold: to examine the effects of E-liquids on the viability and hydrophobicity of oral commensal streptococci, and the effects of E-cigarette-generated aerosols on the biomass and viability of oral commensal streptococci. (2) Methods: Quantitative and confocal biofilm analysis, live-dead staining, and hydrophobicity assays were used to determine the effect on oral commensal streptococci after exposure to E-liquids and/or E-cigarette-generated aerosols. (3) Results: E-liquids and flavors have a bactericidal effect on multispecies oral commensal biofilms and increase the hydrophobicity of oral commensal streptococci. Flavorless and some flavored E-liquid aerosols have a bactericidal effect on oral commensal biofilms while having no effect on overall biomass. (4) Conclusions: These results indicate that E-liquids/E-cigarette-generated aerosols alter the chemical interactions and viability of oral commensal streptococci. Consequently, the use of E-cigarettes has the potential to alter the status of disease and health in the oral cavity and, by extension, affect systemic health.